Nanoscale Au-ZnO Heterostructure Developed by Atomic Layer Deposition Towards Amperometric H(2)O(2) Detection - Xu, Hongyan (Nanoscale Res Lett, 2020)
ABSTRACT: Nanoscale Au-ZnO heterostructures were fabricated on 4-in. SiO(2)/Si wafers by the atomic layer deposition (ALD) technique. Developed Au-ZnO heterostructures after post-deposition annealing at 250 °C were tested for amperometric hydrogen peroxide (H(2)O(2)) detection. The surface morphology and nanostructure of Au-ZnO heterostructures were examined by field emission scanning electron microscopy (FE-SEM), Raman spectroscopy, atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), etc. Additionally, the electrochemical behavior of Au-ZnO heterostructures towards H(2)O(2) sensing under various conditions is assessed by chronoamperometry and electrochemical impedance spectroscopy (EIS). The results showed that ALD-fabricated Au-ZnO heterostructures exhibited one of the highest sensitivities of 0.53 μA μM(−1) cm(−2), the widest linear H(2)O(2) detection range of 1.0 μM–120 mM, a low limit of detection (LOD) of 0.78 μM, excellent selectivity under the normal operation conditions, and great long-term stability. Utilization of the ALD deposition method opens up a unique opportunity for the improvement of the various capabilities of the devices based on Au-ZnO heterostructures for amperometric detection of different chemicals. GRAPHICAL ABSTRACT: [Image: see text]